Assessment of future groundwater quality using GIS for Bhimrad area of Surat City (India). (18th September 2019) - Desai, Manisha D.; Patel, Jayantilal N.
Declination of water quality has become a global issue of concern as with the growth of human population, industrial and agricultural activities expand. The Bhimrad area of Surat City (Gujarat) is highly affected by ground water pollution because of its location in the vicinity of the industrial zone. There exists a creek adjoining Arabian Sea, in which all the wastewater of the city, including that of the industrial area is discharged, thus polluting land and other sources of water in the surrounding areas. This research paper aims to analyse groundwater dilution used under the threat of pollution by identifying the prospects for improving the quality through artificial recharging that may impact groundwater quality. Calculation of percentage reduction in the groundwater quality parameters after recharging was carried out through which estimated improvement in GWQI using GIS, GWQI after recharging is analysed for the years 2015 to 2050.